It Is Not Only About Grievances: Emotional Dynamics in Social Media During the Brazilian Protests - Costa, Jean; Rotabi, Rahmtin; Murnane, Elizabeth; Choudhury, Tanzeem (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
In the summer of 2013, Brazil experienced a period of conflict triggered by a series of protests. While the popular press covered the events, little empirical work has investigated how first-hand reporting of the protests occurred and evolved over social media and how such exposure in turn impacted the demonstrations themselves. In this study we examine over 42 million tweets shared during the three months of conflict in order to uncover patterns in online and offline protest-related activity as well as to explore relationships between language-use in tweets and the emotions and underlying motivations of protesters. Our findings show that peaks in Twitter activity coincide with days in which heavy protesting took place, that the words in tweets reflect emotional characteristics of protest-related events, and less expectedly, that these emotions convey both positive as well as negative sentiment.